Design and evaluation of a wedge-shaped adaptive knee orthosis for the human lower limbs - Zhou, Xin; Liu, Xiaoli; Hao, Jiaxin; Liu, Yu; Tang, Yunqi (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction The incidence of knee osteoarthritis (KOA) is moderately correlated with age and body weight and increases with life span and weight gain, associated with tearing and wearing the knee joints. KOA can adjust the force through the human lower limbs, redistribute the load of the knee joint, reduce the pain, and restore mobility when the arthritis changes are mild. However, most of the existing knee orthosis cannot be adjusted adaptively according to the needs of patients. Methodology This study establishes a biomechanical model of the knee joint to analyze the medial and lateral forces acting on the joint. The new adjustable knee orthosis is designed. It applies the principle of four-point bending to apply pressure to both sides of the knee joint, thereby adjusting the varus angle and modifying the medial and lateral forces on the knee joint. Through structural optimization, the prototype of the knee orthosis weighs only 324 g. Utilizing three-dimensional scanning technology, discrete point cloud data of the leg surface is obtained, reconstructed, and processed to create a 3D model of the human leg surface. The design ensures a close fit to the human leg surface, offering comfortable wear. A pressure sensing film system is employed to build a pressure sensing test system, where the knee orthosis is worn on a prosthesis for pressure testing to evaluate its ability to adjust knee joint forces. Results The pressure test results demonstrate that the knee orthosis can stably provide an adjustment angle of 0–7° and sustain a maximum force of 10N on both sides of the knee joint over extended periods. A self-developed 8-channel plantar pressure sensing insole is calibrated against commercial plantar pressure sensors. Human wear tests on 15 subjects show that during the operation of the knee orthosis, it significantly adjusts plantar pressures, reducing lateral foot pressures by 22% overall, with more pronounced corrective effects observed in lighter participants. Discussion In this study, a wedge-shaped adaptive knee orthosis was provided for KOA patients. The four-point force principle was used to balance the force between femurs and tibia and adjust the meniscus contact gap. The orthotic appliance has the advantages of simple mechanical structure, adjustable correction Angle and good wearing comfort.